Development of Strategic Management and Accounting Implementation at Village-Owned Enterprises with Regard to Using Former Mining Land - Fathimah, Siti Hasna; Sriyono, Sriyono; Zuhrohtun, Zuhrohtun (Journal of International Conference Proceedings, 2023)
This study aims to delve into the development of strategic management and financial implementation at Village-Owned Enterprises with regard to using former mining land that must be managed for productivity in order to increase revenue villages and accounting procedures must be put in place to make financial reporting easier and of higher quality. Employing a qualitative method with a phenomenological approach and gathering data through literature analysis, direct observations, and intensive interviews. The site research in this study is at Village-Owned Enterprises Manunggal Dadi Mulyo in Kwadungan Gunung, Kledung, Temanggung, Central Java. The results of this study are: (1) The most suitable alternative strategies to be developed for Village-Owned Enterprises Manunggal Dadi Mulyo includes development and promotion strategies, (2) Village-Owned Enterprises Manunggal Dadi Mulyo has not implemented accounting practices yet in accordance with the applicable accounting standards. This problem arises because of limited financial literacy of the Village-Owned Enterprises management regarding the importance of financial reporting.